Radіonuclіde dіagnostіcs of joіnt іnjury іn patіents wіth dіabetes - Orlenko, Valeriia; Іvaskіva, Kateryna; Zubkova, Galyna (ScienceRise: Medical Science, 2020)
There are very few convincing effective ways of early diagnosis of joint lesions today. Radiological changes in the early stages of the disease are absent, other laboratory tests are not specific and do not always correlate with the activity of the inflammatory process. The aim of work was to study with the help of radionuclide method the state of arterial and venous blood flow, the presence of inflammatory processes in the knee and ankle joints in patients with type 1 and 2 diabetes mellіtus. Materials and methods. 152 patients with diabetes were examined. Depending on the type of diabetes, patients were divided into two groups - 58 patients were with type 1 diabetes (19 men and 39 women), with type 2 diabetes - 94 patients (19 men and 51 women). The mean age of patients in the type 1 diabetes mellіtus was 42.3 ± 1.8 years, the duration of diabetes mellіtus was 21.1 ± 1.3 years. In the group of type 2 diabetes mellіtus, the average age of patients was 61.3 ± 1.0 years, the duration of diabetes mellіtus was 13.1 ± 0.9 years. Among the examined patients with type 1 diabetes mellіtus, arthropathy was diagnosed in 34 (58.6 %), the control group was patients without joint damage -24 (41.4 %). In patients with type 2 diabetes mellіtus arthropathy was found in 68 (72.3 %) subjects, joint pathology was not in 26 (27.7 %) patients. The method of radionuclide diagnostics of the lower extremities consisted of two methods: radionuclide angiography and radionuclide scintigraphy. Results. At carrying out radionuclide researches of hemodynamіcs at patients with a diabetes mellіtus 1 type with arthropathies in comparison with patients without defeat of joints there are no changes of a blood-groove in vessels of large and average calibre and also arterioles and capillaries of lower extremities in the presence of the expressed venous outflow disturbances. For patients with type 2 diabetes mellіtus with arthropathies, a significant slowing of blood flow velocity in large and medіum-sіzed vessels, as well as arterioles and capillaries was found, which is accompanied by impaired venous outflow. Conclusions. The applied method of radionuclide diagnostics to assess the state of blood flow and the presence of dіabetes-assocіated arthropathy of the knee and ankle joints with a single injection of radiopharmaceutical is one of the most informative methods of early diagnosis of this pathology, and disorders of venous outflow may be a differential criterion for dіabetes-assocіated arthropathy in patients with type 1 and type 2 diabetes